2009
DOI: 10.1080/09540120802001705
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiretroviral medications and medical care in HIV-infected adults diagnosed with mental and substance abuse disorders

Abstract: This paper examines factors associated with adherence to antiretroviral medications (ARVs) in an HIV-infected population at high risk for non-adherence: individuals living with psychiatric and substance abuse disorders. Data were examined from baseline interviews of a multisite cohort intervention study of 1138 HIV-infected adults with both a psychiatric and substance abuse disorder (based on a structured psychiatric research interview using DSM-IV criteria). The baseline interview documented mental illness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 39 publications
5
105
0
1
Order By: Relevance
“…Little is known about the process and factors involved in taking both types of medication, thus, psychotropic medication may interact with HIVrelated medications in a negative manner (Thompson et al 2006) thus contributing to less continuity of psychotropic medication. This issue is relevant since non-adherence to psychiatric medications was found to be associated with non-adherence to antiretroviral medications in a study of HIV-infected individuals living with psychiatric and substance abuse disorders (Mellins et al 2009). Several studies have in fact shown that the management of psychiatric symptoms, associated with taking psychotropic drugs, is correlated with increased HAART adherence and better medical outcomes (Palmer et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Little is known about the process and factors involved in taking both types of medication, thus, psychotropic medication may interact with HIVrelated medications in a negative manner (Thompson et al 2006) thus contributing to less continuity of psychotropic medication. This issue is relevant since non-adherence to psychiatric medications was found to be associated with non-adherence to antiretroviral medications in a study of HIV-infected individuals living with psychiatric and substance abuse disorders (Mellins et al 2009). Several studies have in fact shown that the management of psychiatric symptoms, associated with taking psychotropic drugs, is correlated with increased HAART adherence and better medical outcomes (Palmer et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Harmful alcohol drinking can also reduce coping skills and increase the likelihood of opportunistic infections [13]. Moreover, HIV-positive people who used illicit substances also had alcohol-use disorders resulting in non-adherence to ART [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies from varying regional settings have identified psychological distress as a barrier to optimal adherence. 46,47 Further in-depth studies in this patient population are needed to understand the impact of psychological function on treatment adherence, and psychosocial interventions (e.g., cognitive behavioral therapy) should be examined. 48 Having sex is an important part of overall health and quality of life, including patients infected with HIV.…”
Section: Venkatesh Et Almentioning
confidence: 99%